Efficacy and safety of CO2 cryotherapy in the treatment of infants with tracheobronchial tuberculosis - Zhao, Yidi; Zhang, Tongqiang; Yang, Nan; Xu, Yongsheng; Guo, Wei (Frontiers in Pediatrics, 2022)
Objective This study aimed to investigate the efficacy and safety of CO2 cryotherapy for lymph node fistula tracheobronchial tuberculosis (TBTB) in infants. Patients and methods A retrospective analysis was undertaken on seven patients with lymph node fistula tracheobronchial tuberculosis who underwent fiberoptic bronchoscopy (FB) interventional therapy in the respiratory department of Tianjin Children's Hospital from July 2012 to July 2020. The efficacy, safety, and prognosis of CO2 cryotherapy intervention for the treatment of lymph node fistula TBTB in infants were summarized and analyzed. Results Seven patients with lymph node fistula TBTB were included in this study. Their ages ranged from 6–13 months. The course of the disease from onset to TBTB ranged from 20 to 70 days. The pathological diagnoses of seven cases by FB combined with tissue biopsy were lymph node fistula TBTB, of which 28.57% (two cases) were in the early stage of rupture and 71.43% (five cases) were in the rupture stage. All patients were treated with CO2 cryotherapy combined with foreign body forceps and local injection drugs based on systemic antituberculosis chemotherapy. Two patients were treated once with CO2 cryotherapy, and five were treated three times. According to the comparison of the clinical symptoms, imaging results, and endoscopic presentations before and after the intervention, six patients achieved clinical cure, and one achieved clinical improvement. No severe intraoperative or postoperative complications were observed. The clinical symptoms, endoscopic findings, radiological manifestations, and quality of life of all patients showed marked improvement. No recurrence occurred after 3–6 months of follow-up with FB. Conclusion CO2 cryotherapy can improve the treatment effect of lymph node fistula in infants with TBTB and reduce the incidence of complications. This treatment is safe and reliable in infants.